2020
DOI: 10.3390/s20174772
|View full text |Cite
|
Sign up to set email alerts
|

Bragg Grating Assisted Sagnac Interferometer in SiO2-Al2O3-La2O3 Polarization-Maintaining Fiber for Strain–Temperature Discrimination

Abstract: Polarization-maintaining fibers (PMFs) have always received great attention in fiber optic communication systems and components which are sensitive to polarization. Moreover, they are widely applied for high-accuracy detection and sensing devices, such as fiber gyroscope, electric/magnetic sensors, multi-parameter sensors, and so on. Here, we demonstrated the combination of a fiber Bragg grating (FBG) and Sagnac interference in the same section of a new type of PANDA-structure PMF for the simultaneous measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Additionally, there are several collected papers aimed at sensing applications. Wu, Z. et al demonstrated Bragg-grating-assisted Sagnac interferometer in SiO 2 -Al 2 O 3 -La 2 O 3 polarization-maintaining fiber for strain–temperature discrimination [ 17 ]. Xu, X. et al proposed and demonstrated a temperature and humidity sensor based on a fluorinated polyimide film and fiber Bragg grating [ 18 ].…”
mentioning
confidence: 99%
“…Additionally, there are several collected papers aimed at sensing applications. Wu, Z. et al demonstrated Bragg-grating-assisted Sagnac interferometer in SiO 2 -Al 2 O 3 -La 2 O 3 polarization-maintaining fiber for strain–temperature discrimination [ 17 ]. Xu, X. et al proposed and demonstrated a temperature and humidity sensor based on a fluorinated polyimide film and fiber Bragg grating [ 18 ].…”
mentioning
confidence: 99%